Targeting fatty acid amide hydrolase as a therapeutic strategy for antitussive therapy. Issue 3 (21st September 2017) - Wortley, Michael A.; Adcock, John J.; Dubuis, Eric D.; Maher, Sarah A.; Bonvini, Sara J.; Delescluse, Isabelle; Kinloch, Ross; McMurray, Gordon; Perros-Huguet, Christelle; Papakosta, Marianthi; Birrell, Mark A.; Belvisi, Maria G.
Cough is the most common reason to visit a primary care physician, yet it remains an unmet medical need. Fatty acid amide hydrolase (FAAH) is an enzyme that breaks down endocannabinoids, and inhibition of FAAH produces analgesic and anti-inflammatory effects. Cannabinoids inhibit vagal sensory nerve activation and the cough reflex, so it was hypothesised that FAAH inhibition would produce antitussive activity via elevation of endocannabinoids. Primary vagal ganglia neurons, tissue bioassay, in vivo electrophysiology and a conscious guinea pig cough model were utilised to investigate a role for fatty acid amides in modulating sensory nerve activation in vagal afferents. FAAH inhibition produced antitussive activity in guinea pigs with concomitant plasma elevation of the fatty acid amides N -arachidonoylethanolamide (anandamide), palmitoylethanolamide, N -oleoylethanolamide and linoleoylethanolamide. Palmitoylethanolamide inhibited tussive stimulus-induced activation of guinea pig airway innervating vagal ganglia neurons, depolarisation of guinea pig and human vagus, and firing of C-fibre afferents. These effects were mediated via a cannabinoid CB2 /Gi/o -coupled pathway and activation of protein phosphatase 2A, resulting in increased calcium sensitivity of calcium-activated potassium channels. These findings identify FAAH inhibition as a target for the development of novel, antitussive agents without the undesirable side-effects of direct cannabinoid receptor agonists. Fatty acid amide hydrolase inhibition as a target for the development of novel, safe antitussive therapy http://ow.ly/l4ZE30dbbB1